Measurement of unsaturated hydraulic conductivity - Ho, Cheah Tien. (2013)
Unsaturated hydraulic conductivity of soil is an important parameter that should be taken into consideration when solving flow problems in saturated-unsaturated soil systems. The most effective way to obtain this property is through direct measurement. However, direct measurement of unsaturated hydraulic conductivity is time consuming and expensive. Therefore, indirect measurement can be used to estimate this property. By measuring soil-water characteristic curve (SWCC) and saturated hydraulic conductivity, unsaturated hydraulic conductivity can be estimated by means of theoretical models. In this study, the soil-water characteristic curve and saturated hydraulic conductivity of six different soils were measured and the results were converted to unsaturated hydraulic conductivity by theoretical models. It is observed from the results that estimated unsaturated hydraulic conductivity data are significantly affected by SWCC best-fit equations and the range that SWCC data are measured.